Surveillance for infectious myonecrosis virus in Indian shrimp aquaculture - Shyam, K. U.; Jeena, K.; PaniPrasad, Kurcheti; Rathore, Gaurav; Tripathi, Gayatri (Indian Journal of Fisheries, 2017)
Disease surveillance programmes provide information on diseases that mitigate aquaculture production. Infectious myonecrosis virus (IMNV) has emerged recently as one of the OIE (Office International des Epizooties), the World Organisation for Animal Health listed viral diseases in penaeid shrimps, caused by dsRNA virus. The present study was conducted to investigate the prevalence of IMNV along the Indian coastal states. Samples of the Pacific whiteleg shrimpÂ Penaeus vannamei and the green tiger shrimp Penaeus monodon were collected from 21 randomly selected active shrimp farms located along the coast using a risk-based two stage random sampling survey. Screening of the sampled shrimps based on nested RT-PCR diagnostic tool, did not detect IMNV in any of the samples examined indicating absence of IMN or IMNV incidence in shrimp aquaculture along Indian coastal states.